Another mouthful of dust : Egyptological studies in honour of Geoffrey Thorndike Martin - Martin, Geoffrey Thorndike.; Dijk, Jacobus van, 1953- (Orientalia Lovaniensia analecta, 2016)
This book contains twenty-nine articles presented to Geoffrey Martin by his friends and colleagues in celebration of the long and distinguished career of this eminent Egyptologist. The main areas of Professor Martin's scholarly interests are well represented with a wide range of studies on Early Dynastic Egypt and on the history and chronology, art and archaeology of the New Kingdom, often related to his excavations at Saqqara, Amarna, and in the Valley of the Kings. Other essays deal with Old Kingdom mastabas at Giza, Saqqara and Abusir and with the history of Egyptology and early excavators in Egypt. To reflect the recipient's broad Egyptological interests there are also studies on fragments of a shrine of Mentuhotep II from Gebelein and its geographical implications, a Middle Kingdom wooden statue from Asyut, a Twenty-second Dynasty mummy-cartonnage in the Gayer-Anderson Museum, and Thirtieth Dynasty reliefs from the Theban Precinct of Mut. A full Bibliography of Geoffrey Martin's publications is also included.